Overwintering Larval Cold Tolerance of Sirex noctilio (Hymenoptera: Siricidae): Geographic Variation in Northeast China - Chengcheng Li; Jiahe Pei; Jiale Li; Xiaobo Liu; Lili Ren; Youqing Luo (Insects, 2021)
Sirex noctilio (Hymenoptera: Siricidae) is an invasive pest that has spread and established in many regions worldwide. However, its cold tolerance strategy is still unclear. We measured the supercooling point (SCP) and the lower lethal temperature (LLT) of overwintering S. noctilio larvae during three overwintering periods in four geographically separated populations in China. In addition, using the statistical analysis of the local historical temperature data, we also conducted comprehensive studies of S. noctilio cold tolerance variations and strategies. We measured the SCP of all samples as S. noctilio could survive at its SCP during a short period of exposure (<48 h) and its cold tolerance strategy was freeze-avoidance. The average SCPs of the groups in different spatiotemporal scales were significantly related to average temperature variation with most individuals exhibiting stronger cold hardiness at low ambient temperatures. S. noctilio exhibited a strong cold tolerance and it has the ability to withstand lower temperatures in cold environments. The geographic population showed a positive tendency as the ambient temperature decreased, which would increase its chance of developing in cold regions.